Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1742395319859395
|View full text |Cite
|
Sign up to set email alerts
|

Group-based storytelling in disease self-management among people with diabetes

Abstract: Objective We explored the underlying mechanisms by which storytelling can promote disease self-management among people with type 2 diabetes. Methods Two, eight-session storytelling interventions were delivered to a total of eight adults with type 2 diabetes at a community health center in Toronto, Ontario. Each week, participants shared stories about diabetes self-management topics of their choice. Using a qualitative descriptive approach, transcripts from each session and focus groups conducted during and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The reduction in loneliness is supported by past evidence [ 8 ]. In addition, past reviews have identified that storytelling interventions can enable coping and enhance knowledge [ 10 ] and provide an opportunity to express and understand true experiences and feelings related to the illness [ 10 , 23 ]. Additionally, storytelling has been reported to reduce psychological distress and allowed fears and worries to be discussed [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reduction in loneliness is supported by past evidence [ 8 ]. In addition, past reviews have identified that storytelling interventions can enable coping and enhance knowledge [ 10 ] and provide an opportunity to express and understand true experiences and feelings related to the illness [ 10 , 23 ]. Additionally, storytelling has been reported to reduce psychological distress and allowed fears and worries to be discussed [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social and internal mechanisms identified within the current review have also been identified and supported by past review evidence in chronic illnesses. For instance, self-reflection has been identified as a key process and mechanism through which positive impacts of storytelling can be found, as it allows participants to create and re-create plots of their own story [ 8 , 10 , 23 ]. Further to this, social comparisons can help change the perception of their own situation and make the individual feel less isolated [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This condition was influenced by the patients' motivation and perceptions about the importance of introducing DM interventions. It was influenced by the interaction between patients or patients with nurses (professionals) when giving material (35)(36)(37). Peers share experiences in controlling blood glucose (38) and improve the self-management of patients with DM (34,39).…”
Section: Discussionmentioning
confidence: 99%